Some technical aspects of the rheological properties of high concentration fine suspensions to avoid environmental disasters - Faitli, József; Gombkötő, Imre (Journal of Environmental Engineering and Landscape Management, 2015)
The behavior of slurries and suspensions made by mixing solid particles and liquids is very important for various industrial applications. The latest accidental failure events at tailings facilities (Kolontár, Baia Mare) have focused public interest into this field. Nowadays, environmental practice is turning to use dry deposition techniques or at least as high concentration slurries or pastes as possible, to avoid large spills in case of an accidental failure of an embankment. High concentration slurries are becoming widely accepted in many environmentally related operations such as underground backfilling or simple tailings deposition. However, the hydraulic transport of pastes or high density slurries requires higher energy input via pumps, and, in addition, the energy requirement or pressure loss calculation methods are also different because the rheology of pastes differs from that of dilute slurries. At the University of Miskolc, Institute of Raw Materials Preparation and Environmental Processing, Miskolc, Hungary, this topic has been studied for many decades. The fine suspension – coarse mixture flow model was introduced, and it has been determined that the flow behavior of fine suspensions made of solid particles smaller than a limit particle size can be measured and interpreted in almost the same way as for single phase clear liquids. Based on these measured rheological parameters of fine suspensions, the frictional energy loss can be calculated. The aim of this paper is to give a summary and data base about the rheological behavior of different industrial materials based on pilot scale hydraulic loop measurements. An Anton-Paar rotational viscometer and a tube viscometer with three measuring pipe sections,– developed by our institute – were used for testing. The results of measurements of various granular materials, such as sands, fly ashes, perlite, tailings and red mud are presented in connection with environmental applications. Based on these results, empirical relationships are presented, where the parameters are determined by simple function fitting into the data of measurements carried out at discrete concentration values. The rheology of fine suspensions of any concentration up to the measured maximum can be calculated by these relationships.